Improving Civics Learning Outcomes Through the Scramble Learning Model for Class V Students Elementary School - Murjinah, Murjinah; Choerifki, Siti (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to improve Civics (Citizenship Education) learning outcomes using the scramble learning model for fifth grade students at Prawirotaman Yogyakarta State Elementary School Methodology: This research is ex-post researchThis type of research is classroom action research. The research subjects were 17 students in class V of Prawirotaman State Elementary School, Yogyakarta. Data collection methods in research include tests, observation and documentation. The research instruments are tests and learning implementation sheets. The data analysis technique used is quantitative and qualitative descriptive. The indicator of the success of the action is marked by ≥75% of the total number of students who took part in the learning process having obtained a score of ≥75. Main Findings: The main finding of this research is improvementCivics learning outcomes for fifth grade students at Prawirotaman State Elementary School, Yogyakarta after using the scramble learning model in cycle I and cycle II.Based on test results in implementing learning with modelsscramble learning , students who achieved a score of ≥75 were 70.59% in cycle I and increased to 88.24% in cycle II. The increase in learning outcomes occurred after improvements in actions in cycle II, namely the teacher divided the groups more clearly, the number of group members was reduced, andgiving rewards to calm students. The action is dismissed on the cyclebecause it has achieved the success criteria. Novelty/Originality of this study: The Scramble learning model is designed to improve understanding of concepts. Research can evaluate the extent to which Civics learning outcomes have improved, especially in understanding the concept of citizenship.